Analysis of the Potential of Beef Cattle Business Development in Indramayu District - Fitri Dian Perwitasari; Ahmad Romadhoni Surya Putra; Bambang Suwignyo; Rini Widiati (ANIMAL PRODUCTION, 2021)
This study aimed to analyze the potential for cattle business development in Indramayu Regency. The research locations selected using purposive sampling method were based on the following criteria: (1) Indramayu Regency is the 2nd largest rice producers in the Province of West Java, (2) The area covers 2,099.42 km2 based on secondary data obtained from BPS Indramayu Regency in numbers and (3) The area of agricultural land is still larger than the area of resident housing. The data analysis method used the carrying capacity index (IDD) and Location Question (LQ) analysis formulas. The data were processed and explained descriptively. The results of this study resulted in carrying capacity values consisting of 3 patterns, namely the highest carrying capacity value > 20,000 AU (Gantar and Terisi). Medium carrying capacity value > 10,000 AU (Cikedung and Gabuswetan). Low value carrying capacity 5.000-10.000 AU (Haurgelis, Suyeg, Juntiyuat, Bongdua, Kertasemaya, Patrol, Kedokanbunder and Sindang). The results of the analysis of IDD > 2 there are 12 sub-districts, meaning that based on the availability of forage feed from agricultural land, it is included in the safe category to increase the population of beef cattle. The potential for beef cattle development in Indramayu Regency needs to be prioritized in 12 sub-districts with LQ > 1 and IDD > 2 accompanied by government policies to support investment in livestock marketing facilities and infrastructure for smallholders.